Putatively benign copy number variants in subjects with idiopathic autism spectrum disorder and/or intellectual disability - Qiao, Y.; Harvard, C.; Riendeau, N.; Fawcett, C.; Liu, X.; Holden, J.J.A.; Lewis, M.E.S.; Rajcan-Separovic, E. (Cytogenetic and genome research, 2008)
Putatively benign copy number variants (bCNVs) can be broadly defined as DNA copy number gains or losses that do not lead to a recognizable clinical phenotype. Detection of bCNVs in genomes of clinically healthy individuals is increasing with the widespread use of whole genome arrays of different resolutions and the use of sequence comparison methods. However, the role of bCNVs in human disease susceptibility and phenotype diversity is mostly unknown. In order to explore a potential role of bCNVs in the susceptibility to and/or pathogenesis of human neurodevelopmental disorders we examined the frequency and type of common bCNVs (detected in ≥2 independent control studies) amongst 221 subjects with an autism spectrum disorder (ASD) and/or intellectual disability (ID) in comparison to 40 controls using three array platforms of increasing resolution (Spectral Genomics (1 Mb), Agilent (0.03 Mb) and NimbleGen (0.01 Mb)). We determined that the number of bCNVs/subject, type and frequency of most common bCNVs were similar for both the test and control cohorts when the same array platform was used. The comparison of the ‘load’ of bCNVs (i.e. number/subject) to a standardized metric of phenotypic features (see de Vries et al., 2001) in 91 ASD subjects revealed that a phenotype score ≥4 is significantly more common (P < 0.05) in persons with an ASD having one or more bCNVs via 1 Mb array-CGH, whereas individuals without any recognizable bCNVs are significantly more likely to have a less complex phenotype and a score ≤3. Finally, we report 14 CNVs found amongst our ASD and ID cohorts that are infrequent in neurodevelopmentally normal controls and are of familial origin, thus comprising rare CNVs of unknown significance. Two of these rare familial bCNVs revealed variation in size when transmitted from parent to child, indicating genomic instability. The ongoing discovery and correlation of the pathogenic versus putatively benign underpinnings of the human genome, its inherent variability and potential gene, positional and epigenetic influences will continue to improve our understanding of genome plasticity and its influences on human neurodevelopmental disorders.